A ANALYSIS OF WOMEN'S AEROBIC EXERCISE ON BODY IMAGE AND HIP CIRCUMFERENCE RATIO - Agneta Grace Sesilia; Berlian Agatha Silalahi; Habibi Hadi Wijaya (Universitas Negeri Jakarta, 2025)
Background. Physiological changes in perimenopausal women often affect body image perception and body fat distribution, particularly the hip-to-waist ratio (HTR). Objectives. This study aims to analyze the effect of aerobic exercise on body image and HTR in perimenopausal women. Method. The method used was a literature review, involving the collection and analysis of relevant literature sources from 2020 to 2025 in the form of full-text articles. Results. The analysis results indicate that aerobic exercise does not significantly affect HTR reduction but has a positive impact on improving body image, particularly in women with overweight. The lack of significant effect on HTR is likely due to the natural decline in metabolism during the perimenopausal age, as well as uncontrolled dietary patterns and lifestyle. Conclusion. Although it does not directly reduce RLP or depression levels, aerobic exercise remains a beneficial physical activity for maintaining physical fitness and fostering a positive body image. This study contributes to the understanding that the effectiveness of aerobic exercise is optimized when combined with a balanced diet and the adoption of a healthy lifestyle among middle-aged women.